Generation of two homozygous SHOX2 knock-out human induced pluripotent stem cell lines using CRISPR/Cas9 - Rädecke, Kristin; Gore, Ambuj; Burau, Karin; Laugsch, Magdalena; Köhler, Katrin; Rappold, Gudrun; Hoffmann, Sandra (Stem cell research, 2023)
SHOX2 is a homeobox transcription factor associated with atrial fibrillation (AF) and sinus node dysfunction. Here, we generated two homozygous SHOX2 knock-out hiPSC lines from a healthy control line and a corrected AF patient line (disease-specific SHOX2 mutation corrected to WT) using CRISPR/Cas9. These cell lines maintained pluripotency, an ability to differentiate into all three germlayers and a normal karyotype, presenting a valuable tool to investigate the impact of a full SHOX2 knock-out with respect to arrhythmogenic diseases on a cellular level.
Online verfügbar 30. März 2023, Artikelversion 5. April 2023
Gesehen am 13.06.2023